TIPOLOGI SEBARAN PERILAKU PEMBAKARAN LAHAN GAMBUT DI KABUPATEN KUBU RAYA DAN KABUPATEN BENGKAYANG PROVINSI KALIMANTAN BARAT - Wanti, Fitrianti; Maswadi, Maswadi; Oktoriana, Shenny; Maulidi, Maulidi; Hazriani, Rini; Raharjo, Dwi; Zulfita, Dwi; Krisnohadi, Ari; Hiromitsu, Kuno; Kartika, Anna Silviyana; Manik, Sahat Irawan (Jurnal Social Economic of Agriculture, 2014)
The purpose of this study was to analyze (1) the correlation of factors that affect the spread of forest fire indication, and (2) the pattern of distribution, land burning time, and the public perception of combustion in Kubu Raya and Bengkayang Districts. The research activities were carried out in 12 villages in Kubu Raya and Bengkayang Districts during the month of November 2014 until January 2014. The research method is using correlation analysis and descriptive to explain the distribution patterns, land burn time, and the public perception of combustion. The results showed: 1) there is a relationship between the purpose of combustion (open land and eradicate weeds) with the population, and there is no relationship between the objectives of land combustion on the combustion behavior of the land associated with the main types of cultivated plants, and there is a correlation to the density of hotspots, the density of dry land farming and bush, shrub/ swamp density, marsh density, density of plantation, and density of open land. 2) The pattern of the farmers burning rice, horticulture and perenninal crops were classified into the type of the pattern of spots and the perception is part of a burning activities,  type with ash beds and lodge with the perception of not being a part of burning activities, and type with only one time burning on the stages of land preparation, and type with in the eradication of weeds. Keywords: Peat fires, Land burning behavior, Climate Change Mitigation